Why Not Persuade the Skeptic?: A Critique of Unambitious Epistemology - Veber, Michael (International journal for the study of skepticism, 2019)
What constitutes a solution to the problem of skepticism? It has been traditionally held that one must produce an argument that would rationally persuade skeptical philosophers that they are mistaken. But there is a trend in recent epistemology toward the idea that we can solve the problem without giving skeptics any good reason to change their minds. This is what I call unambitious epistemology. This paper is a critique of that project.